Integration of time and space in historical prose (Eurasian Journal of Philology Science and Education, 2023)
The article comprehensively analyzes that time and space are a set of mobile concepts. In historical novels, the essence of the connection between space and time is highlighted. A deep analysis of the specifics of the originality of the relationship of space and time in historical works has been carried out. Since the very nature of the work is formed into a historical event, the relationship between space and time is self-organized here. In describing and depicting the historical situation in the established chronology, the author proposes a peculiar model. For example, in the historiography of Genghis Khan, a broad commentary on the era is given. The author goes beyond the time and space outlined by him, describes the period before the birth of Genghis Khan, analyzes and completes the details, comparing the time in the story with the period of major events. At the same time, all types of models of space and time are intertwined in the work. Since the historical novel is built mainly on truthful data, documentary, consistent materials, the originality of the spatial, temporal connection is emphasized here. The article seeks concreteness, consistency, convergence of the author between artistic time and real time, differentiation of dynamic events, establishment of relations of the past, present and future.      Keywords: space, time, relativistic concept, habitat, parent settlement